Snapshot The Lens & me. - Carroll, Peter (Alice Springs, N.T. : Peter Carroll, 2010)
"Peter Carroll is a Photographer based in Alice Springs, Cenral Australia... ...Most places I explore will be expressed through the lens from the intimate patterns, details and interactions within it, to the wider angle for a sense of place. As often as possible I like to take it a step further and see the landscape from above, be it by climbing the nearest mountain or by plane or chopper. This method not only allows me to get to know a place more intimately but also develops a sense of a living, breathing Planet, revealing repeating patterns through scale from the leaf of a tree to the drainage patterns of a mountain range."
"Welcome to where you have arrived"
Title from title screen (viewed on 17 Feb. 2011)
Text and graphics.
Mode of access: Internet via World Wide Web. Available at: http://petercarroll.visualsociety.com
Selected for archiving
Keywords: Carroll, Peter; Photographers -- Australia; Photography -- Australia